2013
DOI: 10.1038/cddis.2013.198
|View full text |Cite
|
Sign up to set email alerts
|

CCL-1 in the spinal cord contributes to neuropathic pain induced by nerve injury

Abstract: Cytokines such as interleukins are known to be involved in the development of neuropathic pain through activation of neuroglia. However, the role of chemokine (C-C motif) ligand 1 (CCL-1), a well-characterized chemokine secreted by activated T cells, in the nociceptive transmission remains unclear. We found that CCL-1 was upregulated in the spinal dorsal horn after partial sciatic nerve ligation. Therefore, we examined actions of recombinant CCL-1 on behavioural pain score, synaptic transmission, glial cell fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 59 publications
1
54
0
Order By: Relevance
“…Moreover, a recent paper by Li et al (2013) has reported that NMDAR activation induced maintenance of OIH is associated with NR1 and NR2B subunits expression, membrane trafficking and function in the spinal cord dorsal horn. The level of NMDA receptors, particularly NR1, in primary sensory neurons increases during inflammation, which contributes to peripheral inflammatory pain sensitization (Tan et al, 2010;Akimoto et al, 2013). Whether peripheral sensitization caused by NMDAR activation is implicated in OIH has been not well reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent paper by Li et al (2013) has reported that NMDAR activation induced maintenance of OIH is associated with NR1 and NR2B subunits expression, membrane trafficking and function in the spinal cord dorsal horn. The level of NMDA receptors, particularly NR1, in primary sensory neurons increases during inflammation, which contributes to peripheral inflammatory pain sensitization (Tan et al, 2010;Akimoto et al, 2013). Whether peripheral sensitization caused by NMDAR activation is implicated in OIH has been not well reported.…”
Section: Discussionmentioning
confidence: 99%
“…The SG was easily discernible with transmitted illumination as a relatively translucent band across the dorsal horn in the transverse slice preparations. Blind whole-cell voltage-clamp recordings were made from SG neurons, as previously described (36). The pipette solution contained 135 mM K-gluconate, 5 mM KCl, 0.5 mM CaCl 2 , 2 mM MgCl 2 , 5 mM EGTA, 5 mM Hepes, and 5 mM ATP-Mg, pH 7.20, with KOH.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, neuropathic pain significantly lowers the life quality of patients [14][15][16][17][18]. Recent studies have shown that there is activation of peripheral and central gliocytes complicated with release of inflammatory cytokines in neuropathic pain.…”
Section: Cell Biochem Biophysmentioning
confidence: 99%